THE INNER CONFLICT: CONSCIENCE OR STATE'S RULE - RB. Edi Pramono (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
Conflict is part of human life. No one can get rid of it. Some conflicts end in good resolution, some end in bad resolution, and some end in tragedy. Antigone, the main character, is encountering a dilemma of whether to keep on the conscience of burying her brother or to obey her king’s edict forbidding her to bury him otherwise death sentence she has to bear. This inner conflict represents the power relation between Antigone and the king. Foucault proposes that power relation comprises the productivity of power and the constitution of subjectivity. He also says that resistance is an endemic fact in the world of power relations. Furthermore, Kabeer states that the power of women signifies the ability of women to make choices. In determining choices, Antigone experiences inner conflict, and thus, she encounters a double struggle, i.e., against herself and against Creon, the king. With the knowledge that conscience or heaven's values are higher than man’s rule or earth’s values, Antigone seizes her power to deal with her conflicts. The conflict between Antigone and Creon, which is first between heaven and earth laws, turns out to be a conflict mostly covered by self-pride. This contestation of power leads her to agony and suicide, and this confirms that inner conflicts in power relations may end in tragedy.